A push–pull silafluorene fluorophore for highly efficient luminescent solar concentrators. Issue 59 (26th July 2017) - Gianfaldoni, Federico; De Nisi, Francesca; Iasilli, Giuseppe; Panniello, Annamaria; Fanizza, Elisabetta; Striccoli, Marinella; Ryuse, Daiki; Shimizu, Masaki; Biver, Tarita; Pucci, Andrea
Abstract : We report on the preparation of luminescent collectors based on poly(methyl methacrylate) (PMMA) thin films doped with a red-emitting 2-amino-7-acceptor-9-silafluorene, where the amino group is –N(CH3 )2 and the acceptor is –CHC(CN)2 . Abstract : We report on the preparation of luminescent collectors based on poly(methyl methacrylate) (PMMA) thin films doped with a red-emitting 2-amino-7-acceptor-9-silafluorene, where the amino group is –N(CH3 )2 and the acceptor is –CHC(CN)2 . The results obtained from photophysical investigations of the dye in different solvents and in PMMA are very encouraging as the silafluorene dyes turn out to be highly dispersed in the solid matrix, stable upon irradiation and highly emissive. QY and lifetime investigations demonstrate that autoabsorption phenomena moderately occur with SilaFluo content, and the optical features still maintained very significant, also at the highest fluorophore concentration (QY ∼ 65%). Study of the LSCs features yields excellent optical efficiencies of 9.6% attained for 25 μm thick PMMA films containing the 1.5 wt% of SilaFluo. This performance is at the top level with respect to the current state-of-art of similar devices based on perylene-based fluorophores such as Lumogen Red.